2020
DOI: 10.1002/chem.202001379
|View full text |Cite
|
Sign up to set email alerts
|

Systematic DFT Studies on Binary Pseudo‐tetrahedral Zintl Anions: Relative Stabilities and Reactivities towards Protons, Trimethylsilyl Groups, and Iron Complex Fragments

Abstract: Binary pseudo‐tetrahedral Zintl anions composed of (semi)metal atoms of the p‐block elements have proven to be excellent starting materials for the synthesis of a variety of heterometallic and intermetalloid transition metal–main group metal cluster anions. However, only ten of the theoretically possible 48 anions have been experimentally accessed to date as isolable salts. This brings up the question whether the other species are generally not achievable, or whether synthetic chemists just have not succeeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 104 publications
1
21
0
Order By: Relevance
“…Both (PbBi 3 ) − and (Pb 3 Bi) 3− can be viewed as being built up by a triangular base of one atom type, which is then capped by a single atom of the second atom type. As shown in one of our earlier studies, the relative stability of such anions with a 1:3 or 3:1 atomic ratio depend on the respective covalent radii of the involved elements 21 . In the case presented here, however, this should play a minor role only, as the difference of the covalent radii of Pb and Bi is negligible.…”
Section: Resultssupporting
confidence: 58%
“…Both (PbBi 3 ) − and (Pb 3 Bi) 3− can be viewed as being built up by a triangular base of one atom type, which is then capped by a single atom of the second atom type. As shown in one of our earlier studies, the relative stability of such anions with a 1:3 or 3:1 atomic ratio depend on the respective covalent radii of the involved elements 21 . In the case presented here, however, this should play a minor role only, as the difference of the covalent radii of Pb and Bi is negligible.…”
Section: Resultssupporting
confidence: 58%
“…Hence, the (Ge 3 As) 3À unit binds with all three Ge atoms, and the (Ge 2 As 2 ) 2À ligands involve two Ge atoms and one As atom each. In a recent comprehensive study of binary pseudotetrahedral anions, [26] we inspected the atomic orbitals of all different elemental combinations. The Ge-Ge bonds contribute predominantly to the HOMOs of these anions, so their involvement in the coordination is obvious.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed recently, the ratio of the atomic radii seems to play a role for the (relative) stabilities of binary pseudotetrahedral anions. [26] Hence we analyzed the results obtained for E XR in this regard, and found that within a series of a given Tt, the course of the E XR values indeed can be reproduced this way: obviously, for smaller differences of the covalent radii, the exchange reactions become more exoenergetic (Table S9). Hence anions with a 3:1 or 1:3 ratio of the involved atom types are stabilized more efficiently in comparison to the anions with a 2:2 atomic composition, if the sizes of the involved atoms are more similar; we attribute this to the fact that the 3:1 and 1:3 anions can be understood as triangles of one atom type with a single atom of the other type capping it, for which the size difference matters more than for two TtÀTt or PnÀPn "dumbbells" forming the 2:2 anions.…”
Section: Angewandte Chemiementioning
confidence: 90%
“…This finding is also in agreement with previous experimental results 76,104,115 and the predictions from previous computational studies. 94 The highest occupied molecular orbital (HOMO) is located along the Tt-Tt bond, thus being prone to an electrophilic attack by an Au + cation, as in this case. Upon bridging, the Sn-Sn and Pb-Pb bonds are significantly elongated compared to the parent pseudo-tetrahedral anions by about 20 pm.…”
Section: (Pseudo-)tetrahedral Zintl Anions As Ligands Of D 10 Metal Atomsmentioning
confidence: 96%
“…Another benefit of the reduced negative charge of the (Tt 2 Pn 2 ) 2and (TrBi 3 ) 2anions is the possibility to perform follow-up chemistry in room-temperature solvents, such as ethane-1,2-diamine (en), pyridine (py), or dimethylformamide (dmf). All of the named species show considerable reactivity towards d-block or f-block organometallic or coordination compounds, which has been extensively explored in the past decade.25,26,31,32,34,38−43,65,77−93 Besides, several further pseudo-tetrahedral anions, (TrTt 3 ) 5-(Tr = Al, Ga; Tt = Ge, Sn, Pb), (InTt 3 ) 5-(Tt = Sn, Pb), (TlPb 3 ) 5-, (TrPn 3 ) 2-(Tr = Al, Ga; Pn = As, Sb), (TlSb 3 ) 2-, (Si 2 Pn 2 ) 2-(Pn = P, As), and (Ge 2 Sb 2 ) 2-, were predicated to be generally synthesizable, which is yet to be proven 94.…”
mentioning
confidence: 97%